Theory of remote non-destructive monitoring thermophysical properties of different objects using flash techniques; Математическое и физическое моделирование опасных природных явлений и техногенных катастроф - Troitsky O. Yu. Oleg Yurievich (2012, 2012)
В фонде НТБ ТПУ отсутствует